SPIRITUALITY AND THE UNIVERSITY - Kourie, Celia (Asian Horizons, 2011)
Without doubt, “spirituality” is in high demand; it is no longer a phenomenon discussed quietly and reservedly in church circles, but has increasingly entered the public arena. It is no longer limited to clergy, religious workers, theologians and theoreticians of religion, but on the contrary is a topic of discussion in the health profession;2 by psychologists;3 in business;4 and in education5 – to mention but a few areas of research. Suffice it to say that spirituality has come into its own; publications in the field, both popular and scholarly, abound; courses on spirituality and retreats are in high demand; and centres for the study of spirituality have been instituted to cater for this growing interest. In addition to the foregoing, the academic study of spirituality has come increasingly to the fore, and will be the main focus of discussion for this paper. It addresses, inter alia, such questions as the following: What is spirituality in general? What is Christian spirituality? How is Christian spirituality taught in the Academy? What methodological approaches are best suited to the academic study of spirituality?